Mycobacterium Bovis: Prevalence patterns and risk factors in East Darfur State - Mudather Elnoor Younis; Mohamed Elhaj Abdurrahman; Abu baker Mohamed Yahya; Esam Eldin Adam Abdoelkarim; Hassen Abdalla Abdalrahim; Ahmed Jbril Aldooma (International Journal of Health and Social Behavior, 2025)
Mycobacterium Bovis is a serious infection that affects cattle and has ramifications for human health, especially in areas where close contact between humans and animals is widespread and pasteurization of dairy products is not widely used. The purpose of this work is to identify risk factors connected with M. bovis infection, estimate the prevalence of the disease in east Darfur State, and underline the main aspects of the disease. The study included a total sample size of 100 cows milk collected from different localities of East Darfur State in Sudan ( Abu Matarq 21.1%, Yaseen 15.3%,El-Daein 22.1%, Abu Karinka 6.8% and Assalaya 5.1% ) this study estimated that 25% of the collected raw milk specimen was positive for mycobacterium. The incidence of Mycobacterium Bovis in Sudan is the result of a complex interaction of cattle management techniques, environmental conditions, and public health initiatives. While there is increased knowledge of the disease and efforts to control it, obstacles such as limited resources, cultural customs, and environmental stressors continue to impact its tendencies.